PIB, économie de la drogue et territoires - Assen Slim (EchoGéo)
In May 2018, INSEE decided to integrate the drug economy into the calculation of GDP. This reform is part of a larger project aimed at comparing national territories within the EU as well as regional territories (and / or metropolises) within countries. However, it poses serious methodological problems both for the collection of data and their interpretation. Moreover, it does not bring any significant clarification progress on the real questions raised for years by the GDP indicator.